Analysis of the Implementation of a Construction Quality Management System Based on ISO 9001: 2015 at PT Murni Karya Mandiri - Sutria Desman; Lina Febyanti; Elvi Syamsuir (LEADER: Civil Engineering and Architecture Journal, 2023)
The Government of the City of Bukittinggi is committed to implementing the Construction of the 2019 Public Service Mall Office Building as a concrete action in an effort to improve the quality of public services. The Public Service Mall is a form of commitment in order to improve services to the public and solutions for integrated services that are currently not integrated between central and regional services as well as business services in one place. The importance of an organization for a project is the main reason the author made a thesis that refers to ISO 9001: 2015. This standard refers to quality design, quality management and quality assurance for a variety of different companies. The ISO 9000 standard includes discussion of risks, costs, benefits, management responsibilities, quality system principles, and other blocks that help promote quality standards according to real situations. This chapter describes the results and discussion of the analysis of the application of quality management systems at PT. Murni is an independent work based on ISO 9001: 2015. The data source obtained by the author is based on the results of interviews with 6 (six) stakeholders consisting of contractors, supervisory consultants, chief craftsmen and workers who served at PT Murni Karya Mandiri on the Bukittinggi City Public Service Mall Development Project. Analysis of the application of the quality management system refers to the principle of ISO 9001: 2015 as outlined in 7 (seven) clauses. ). The construction of the Public Service Mall is targeted for 6 months of working days starting from June 15 to December 12, 2019. With consultations, the supervisor is CV Intikarya Tigamitra. The signing of the contract as well as the handover of the field to mark the start of construction work was carried out by the Bukittinggi City Government at the Mayor's Official House behind the beam. (bukittinggi.go.id).